Rapid desensitisation of the GH secretagogue (ghrelin) receptor to hexarelin in vitro. - Orkin, R; New, D; New, D; Norman, D; Norman, D; Chew, S; Chew, S; Clark, A; Clark, A; Grossman, AB; Grossman, AB; Korbonits, M; et al. (2003)
Ghrelin, the recently identified hormone with GH-secreting and appetite-inducing effects, acts on the GH secretagogue receptor (GHS-R). GHS-R belongs to the G protein-coupled 7 transmembrane domain receptors and activates the phospholipase C pathway; it then leads to the release of GH from somatotroph cells via an elevation of intracellular calcium concentration. Both in vivo and in vitro studies demonstrated that the effect of GH secretagogues (GHS) could be desensitised similar to most receptor stimulation systems. We have studied whether acute desensitisation of the GHS-R occurs in response to the GHS hexarelin in vitro in terms of intracellular calcium concentration. Chinese hamster ovary cells were transiently transfected with cDNA encoding the human type 1a GHS-R. The presence of messenger RNA was confirmed with RT-PCR, while no GHS-R was observed in mock-transfected cells. Calcium responses to the peptide GHS analogue hexarelin were measured using the fluorescent indicator fura-2. Cells were stimulated with the peptide GHS, hexarelin, at concentrations between 10(-10) and 10(-7) M. Cells transfected with the GHS-R cDNA demonstrated a significant and specific calcium response to hexarelin that was not observed in mock-transfected cells. Marked desensitisation of the calcium response to hexarelin was observed 2-5 min after the first dose of hexarelin (10(-7) M) was administered. These data show directly for the first time the desensitisation of the GHS receptor signal at the second messenger level. The desensitisation of the receptor may play a major role in the regulation of effect of circulating or locally produced ghrelin both in the GH and in the appetite-regulating system or in other systems where ghrelin has been shown to be active, such as the cardiovascular system or cell proliferation.